2009
DOI: 10.1007/s10620-009-1047-2
|View full text |Cite
|
Sign up to set email alerts
|

Local Immune Regulation of Mucosal Inflammation by Tacrolimus

Abstract: PurposeTacrolimus is a potent immunomodulator that is effective in the treatment of inflammatory bowel disease (IBD). However, potential toxicity and systemic effects with oral intake limit its use. Local tacrolimus treatment is effective in a subgroup of proctitis patients. This study aimed to evaluate whether colonic mucosal immune cells are susceptible to locally applied tacrolimus in vitro. Our in vivo studies aimed at evaluating whether local tacrolimus treatment in mice would bring about local immune sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Again no major side effects were reported and the preparation was well tolerated 29 . The mechanism of action of tacrolimus would also appear to be local, rather than systemic, immune suppression as the administration of rectal tacrolimus inhibits the activation of immune cells within the intestinal mucosa and not systemically 30 . Thus as the studies, and observations, demonstrate encouraging results in a difficult-to-treat patient population, a randomised double-blinded placebocontrolled trial was warranted.…”
mentioning
confidence: 99%
“…Again no major side effects were reported and the preparation was well tolerated 29 . The mechanism of action of tacrolimus would also appear to be local, rather than systemic, immune suppression as the administration of rectal tacrolimus inhibits the activation of immune cells within the intestinal mucosa and not systemically 30 . Thus as the studies, and observations, demonstrate encouraging results in a difficult-to-treat patient population, a randomised double-blinded placebocontrolled trial was warranted.…”
mentioning
confidence: 99%
“…Moreover, a study by van Dieren et al [13] showed that tacrolimus is adsorbed and active in human rectal mucosa. The same authors demonstrated that interleukin-2 can be suppressed in murine colonic (lamina propria) T cells [14] via topical administration of tacrolimus, thus confirming a local mechanism of action. Nonetheless, even with rectal application, raised tacrolimus levels and acute renal injury have been reported [15].…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, an immunosuppression approach that seeks to block the signaling responsible for release of cytokines and inflammatory mediators could be a reasonable approach to halt the inflammation of RC. Furthermore, urothelium is the primary site of tissue damage in the pathophysiology of non‐infectious hemorrhagic cystitis . The pre‐clinical efficacy of this approach was tested in a rodent model of chemically induced HC using tacrolimus.…”
Section: Experimental Modalitiesmentioning
confidence: 99%
“…Late endothelial cell damage and perivascular fibrosis occur as a result of vascular occlusion and bladder ischemia. 8,9 Late radiation tissue injury can take several months to many years to develop, and is largely a function of the total radiation dose and fraction size. The pathological hallmark of late radiation tissue injury is obliterative endarteritis resulting in atrophy and fibrosis.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation